Diet dan Olahraga sebagai Upaya Pengendalian Kadar Gula Darah pada Pasien Diabetes Melitus Tipe 2 di Poliklinik Penyakit Dalam RSUD Ulin Banjarmasin Tahun 2015 - Nany Suryani; Pramono .; Henny Septiana (Jurnal Kesehatan Indonesia, 2016)
Diabetes mellitus (DM) type 2 is a metabolic disorder of the endocrine system, particularly an imbalance glycemic. The type 2 diabetes occurs when the pancreas does not produce enough insulin to maintain normal levels of glucose in the blood or when the body is unable to use the insulin that is produced. The type 2 diabetes disease management through the implementation of the four pillars of diabetes treatment including education, sports, medicine dietary adjustments or dietary nutrients. This study aims to analysis the diet and exercise as an effort to controll blood sugar level. The study design used is the means of analytical investigation with case-control design. The study population was all patients with type 2 diabetes mellitus disease in hospitals Ulin Banjarmasin. A large sample of 34 respondents, including 17 cases and 17 controls. The sampling was conducted by sampling purpose.. Diet data and respondents statements were obtained from interviews with exercise and food recall interlocutor for food intake. Bivariate analysis using the chi-square test. Based on the statistical test it showed no relationship diet to control sugar levels in the blood (p = 0.001), with OR 29, and there is a relationship of exercise on the control of blood sugar levels (p = 0.000), with OR 35. From the results it can be concluded that there is a relationship significant that respondents diet blood sugar is not controlled it will be 29 times greater than those who did not diet and exercise blood sugar respondents will be checked more than 35 times higher than those who did not exercise. Diet and exercise can help to control blood sugar levels and help the most effective treatment.